2017
DOI: 10.2147/jpr.s115449
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acculturation, coping strategies, locus of control, and self-efficacy on chronic pain: study of Chinese immigrant women in Italy – insights from a thematic field analysis

Abstract: Chronic pain represents a common public health concern worldwide. It is a complex phenomenon, owing to the interaction of different factors, including biological, physiological, psychological, environmental, and social variables. Some groups, such as women and immigrants, are particularly vulnerable. However, little is known about how Chinese women in Italy live with and face chronic pain. The present study aimed at filling this knowledge gap by examining the burden of chronic pain in Chinese immigrants in Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Although nociception usually leads to pain, one can exist without the other (eg, congenital analgia). In addition to nociception, the central nervous system considers multiple sensory, emotional, social, and cognitive factors to respond with or without pain, and with less or more pain intensity . Consequently, nociception can be understood as the processing of an afferent stimulus and pain as an efference (ie, response; see Moseley).…”
Section: Introductionmentioning
confidence: 99%
“…Although nociception usually leads to pain, one can exist without the other (eg, congenital analgia). In addition to nociception, the central nervous system considers multiple sensory, emotional, social, and cognitive factors to respond with or without pain, and with less or more pain intensity . Consequently, nociception can be understood as the processing of an afferent stimulus and pain as an efference (ie, response; see Moseley).…”
Section: Introductionmentioning
confidence: 99%
“…Further, host countries with military service members and families from other countries living in their communities also have a responsibility to examine their own biases and care practices when interacting with this population. Establishing an effective therapeutic alliance when accessing a health care system in a new culture can be difficult 24 . Therefore, arming spouses with appropriate expectations may aid in reducing stress if and when they would need to seek care outside the military system.…”
Section: Discussionmentioning
confidence: 99%
“…A previous Spanish study found that the work schedules of Chinese immigrants influenced their eating habits [ 13 ]. In Italy, a study investigated Chinese women and found that working less due to chronic pain is not considered an option to them, since work is extremely important in Chinese culture [ 14 ]. As noted above, there is a large gap for studies in Europe, which may be justified by the difficult access to this population and by the fact that this migration has become more important in the last two decades.…”
Section: Introductionmentioning
confidence: 99%